Challenges confronting beginning researchers in conducting literature reviews. Issue 1 (2nd January 2016) - Chen, Der-Thanq "Victor"; Wang, Yu-Mei; Lee, Wei Ching
Abstract : Conducting literature review is a complicated, sometimes confusing and laborious process that beginning educational researchers, especially graduate students, often find challenging. However, in the past these challenges were hardly considered, but in more recent times they have been increasingly considered by various faculties and graduate schools due to the expanding needs from growing enrolments. To further develop and strengthen the responses to these identified needs, this article reviews literature concerning challenges faced by beginning educational researchers in conducting literature review, aiming to help unpack this complicated phenomenon by constructing a coherent story. Based on our review, we propose a framework to conceptualize four types of challenges. We term them LMCO (linguistic, methodological, conceptual, and ontological) challenges. Discussions centers on the four identified challenges, recommendations for future studies and implications to graduate preparatory programs.